Simplified Analysis of Environmental Permits integrated through OSS - Ai Heni Nuraeni (Jurnal Abdimas Multidisiplin, 2025)
Purpose: This study aims to determine the effectiveness of the Simplification of Environmental Permits which are integrated into business permits through the OSS system. Methodology/approach: This study uses qualitative research methods by tending to use analysis that emphasizes the perspective of the subject. The theoretical basis is embedded as a guide so that the research focus can adjust to the facts on the ground. Results/findings: The Job Creation Law changes the context of environmental permits to environmental approvals. These changes have an impact on the context of environmental feasibility studies, both UKL-UPL and AMDAL. The implementation of the integration of environmental permits into business licenses becomes efficient through OSS. Conclusion: The integration of environmental permits into business licenses under the Job Creation Law simplifies the licensing process, reducing costs and time for businesses. However, this has raised concerns about limited community participation and the potential weakening of environmental protections. While the system aims to balance economic growth with sustainability, it reduces the role of environmental assessments, which may impact long-term environmental governance. Limitation: The limitation of this research is a description of the procedure for integrating environmental permits into business permits through OSS. Contribution: The results of this study are expected to be used as a reference by further researchers in order to develop an analysis of related themes.